1978
DOI: 10.1021/ja00490a019
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystals composed of N-acylamino acids. I. Circular dichroism and selective light transmission in cholesteric liquid crystals composed of N-acylamino acids and organic solvents

Abstract: Optically active '-acylamino acids formed a new type of lyotropic cholesteric liquid crystals when they were swelled and dispersed as a suspension in solvents such as benzene, chlorobenzene, chloroform, and «-hexane. An appropriate solvating ability to swell but not to dissolve any given '-acylamino acid may be a necessary condition for a solvent to form the liquid crystalline phase which appears as a suspension. These suspended liquid crystals showed some characteristics of lyotropic cholesteric liquid crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 5 publications
(9 reference statements)
2
15
0
Order By: Relevance
“…However, we are not aware of any report for the existence of such phase between the V 1 and the L a phase in a ternary phase diagram. The cosurfactant-induced [V 1 L a H 2 O m ] phase transformation observed here is the typical pattern observed in ionic surfactant/alcohol/water systems (49).…”
Section: Phase Transformation Along the Line C (W S 70)supporting
confidence: 73%
See 1 more Smart Citation
“…However, we are not aware of any report for the existence of such phase between the V 1 and the L a phase in a ternary phase diagram. The cosurfactant-induced [V 1 L a H 2 O m ] phase transformation observed here is the typical pattern observed in ionic surfactant/alcohol/water systems (49).…”
Section: Phase Transformation Along the Line C (W S 70)supporting
confidence: 73%
“…Probably, the optical activity in these biopolymers play important role in the biology and chemistry of these assemblies. Therefore, study of the role of optical activity in the self-aggregation of simple and optically-active surfactants, like N-acylaminoacids, would be an important step in understanding more complicated systems which show both micellization and enantiomerism (2,3).…”
Section: Dp Acharya Ma Lopez-quintela H Kunieda Et Almentioning
confidence: 99%
“…A variety of liquid-crystalline materials have been prepared by self-assembly through H-bond formation [53,54]. It has been observed that gelators containing optically active acids and steroidal and condensed aromatic rings form lyotropic liquid crystal [55,56].…”
Section: Polarizing Optical Microscopymentioning
confidence: 99%
“…The results undoubtedly suggest that the triglyceride moiety interacts with the carboxyl group in 12-HSA or stearic acid. Capitani et al (9) studied organogel formation in a lecithin/cyclohexane system by NMR. Steep increases in the viscosity of the system were observed on the addition of small amounts of water.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of low-molecular weight organic substances, such as organometallic complexes (1,2), 12-hydroxystearic acid (12-HSA) (3)(4)(5)(6)(7), dibenzylidene sorbitol (8), various alkylamide derivatives (9)(10)(11), androstanyl derivatives (12,13), anthracenyl derivatives (14,15) and cholesterolbased derivatives (15,16), are known to form organogels with network structures in various organic liquids. These substances are widely utilized as regulators of viscoelastic properties for greases and cosmetics, as solidifier for used cooking oil, and as reagents for the recovery of ocean-spilled oil.…”
mentioning
confidence: 99%